HUBUNGAN TINGKAT PENCAHAYAAN DAN POSTUR KERJA DENGAN KELUHAN NYERI LEHER OPERATOR JAHIT PO. SEVENTEEN GLORY SALATIGA - Alberto Asali; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Complaints of neck pain is pain is located in the posterior region of the cervical spine (C1-C8), of the superior nuchal line until T1 with or without radiation to the head, trunk, and upper extremities. Working posture while sewing as well as the level of lighting in the work area may be a risk factor for neck pain on a sewing operator. The purpose of this study was to analyze the relationship between the level of exposure to the working posture and working posture with neck pain complaints sewing operators. This study uses cross sectional study which is a form of observational study and is analytic descriptive. The sample of the study was 35 sewing operators with total sampling method. Neck pain complaints were measured subjectively using a Visual Analog Scale Questionnaire (VAS). Statistical analysis using Rank Spearman correlation test. The result showed no correlation between lighting level with work posture (p = 0,451). There is correlation between work posture with complaint of neck pain (p = 0,010). Business owners should implement a healthy friday program and a physical examination to maintain the health of workers and detect neck pain complaints on sewing operators. As well as the need for training and additional insight into ergonomic seated work postures, improvements on existing workstations and lighting systems with appropriate criteria.